Adjusting deficiency to nature tourism: the case of a contemporary experience of expeditions using all-terrain wheelchairs (ATW) - Perera, Eric; Villoing, Gaël (Eracle. Journal of Sport and Social Sciences, 2019)
This article looks into All-Terrain Wheelchair (ATW) expeditions carried out in high- mountain environments and the ways of making these possible despite many barriers, both natural and social. Using the life and practices narrative of Jean-François Porret (JFP), the pioneer of ATW in France, this work presents an individual and original experience of nature tourism. Basing ourselves on his personal life story, we will show how JFP adapted his equipment, innovated, but also how he socially adjusted expeditions to disability. JFP was led to reconsidering the practice of mountaineering so as to experience again the old feelings in his ATW, becoming conscious of his “new” body and of the limits associated to his new deficiency. The ATW thus becomes a tool for social interaction in extreme environments where expeditions favour disabled/abled integration in order to overcome the constraints of disability.